2014
DOI: 10.1186/1755-8166-7-28
|View full text |Cite
|
Sign up to set email alerts
|

Rare copy number variations containing genes involved in RASopathies: deletion of SHOC2 and duplication of PTPN11

Abstract: BackgroundRASopathies are a group of disorders related to Noonan syndrome that with dysregulated RAS-mitogen-activated protein kinase (MAPK) signaling pathway. Noonan syndrome (NS, OMIM# 163950) is a both phenotypically and genotypically variable disorder. We and other researchers have demonstrated that copy number variations underlie a small percentage of patients with RASopathies.ResultsIn a cohort of 12 clinically characterized patients with congenital heart defect (CHD) and features suggestive of Noonan sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Still, 15%–20% of the molecular basis of NS remains unexplained. Copy number variations encompassing the locus of one of the known genes associated with NS have been rarely reported27 and could account for a very small amount of the NS unknown aetiology. Alternatively, it remains to be investigated whether digenic inheritance could also play a role in NS aetiology, in which variants in two or more genes of the RAS/MAPK pathway would be required to overcome a threshold of increased ERK signalling, and consequently manifestation of the NS phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Still, 15%–20% of the molecular basis of NS remains unexplained. Copy number variations encompassing the locus of one of the known genes associated with NS have been rarely reported27 and could account for a very small amount of the NS unknown aetiology. Alternatively, it remains to be investigated whether digenic inheritance could also play a role in NS aetiology, in which variants in two or more genes of the RAS/MAPK pathway would be required to overcome a threshold of increased ERK signalling, and consequently manifestation of the NS phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that different pathogenic variants in the RIT1 gene cause autosomal dominant Noonan syndrome through a gain-of-function mechanism resulting in increased RAS/MAPK signaling [Bertola et al, 2014;Gos et al, 2014;Milosavljević et al, 2016;Yaoita et al, 2016]. Recent reports have demonstrated that copy number variations containing disease-causing genes of RAS/MAPK pathway may be a pathogenetic mechanism for the etiology of RASopathies or related disorders [Graham et al, 2009;Luo et al, 2012;Chen et al, 2014]. Although our patient had no typical facial gestalt of Noonan syndrome and presented with atypical anomalies, such as cleft palate and hypoplastic corpus callosum, the RIT1 gene remains one of the candidate genes for her phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In each of these cases, gene duplication is thought to result in increased dosage of SHP2 which has the equivalent effect as the common gain of function mutation in PTPN11 associated with NS. In addition, rare chromosomal duplications associated with SHOC2 in a NS patient [56], and RAF1 and MAP2K2 in patients with mild RASopathy spectrum phenotypes have been reported [57, 58]. Chromosomal deletions have also been reported to be associated with a RASopathy phenotype.…”
Section: Copy Number Variation Associated With Rasopathy Genesmentioning
confidence: 99%